Taḍmīn in the Quranic Versification "Literature Study on the Secrets Letter Jar" | التضمين في النظم القرآني (دراسة في أسرار حروف الجر) - Haniah Mukhtar (Al-Zahra : Journal for Islamic and Arabic Studies, 2014)
The research concludes that the concept of al-taḍmīn in balāghah can provide deepmeaning to a verse of the Quran. Some examples mentioned on this paper in using latterjar, like in surah al-Baqarah/2: 76, word “Khala” connected with latter "ila", which issupposed to connect with "bi"; word “aḥsana” connected with latter “bi”, which is shouldbe connected with “ilā" (al-Qaşaş/28: 77); word “Maşā” connected with letter “fī” whichis should be connected with "alā” (al-Isra/17: 37). The paper reveals that the above usageis more appropriate, because it can describe the true meaning. The method of this paperis based on the content analyses. Referring to the classical references of Naḥw andBalāghah, and the critical reading is a privilege of this paper.